Characteristics of the bat-swing trajectory when hitting a ball toward the same and opposite fields - Morishita, Y.; Yanai, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The purpose of this study was to examine within-subject differences in bat-swing trajectory between intentional hitting towards the same field and towards the opposite field. 19 industrial league baseball batters and 16 collegiate baseball batters performed same-field hitting (SH) and opposite-field hitting (OH). The movement of the bat during the swing was recorded with two high-speed cameras (1000 fps) for 3D analysis. At the instant of ball impact, the striking surface of the bat faced towards the same field in SH and towards the opposite field in OH. The bat-head trajectory immediately before impact was directed obliquely upward in SH, whereas it was directed obliquely downward in OH. Throughout the swing, the projection angle of the bat on the vertical plane was greater in OH than in SH, and the ratio of the translational component of the bat-head speed to the resultant bat-head speed was significantly greater in OH than in SH. These results suggest that the characteristics of the bat swing in OH provide a suitable impact condition to drive the ball towards the opposite field, as evidence has demonstrated that (1) a batted ball is likely to travel towards the opposite field when the lower half of the ball is hit by a vertically inclined bat, and (2) the striking surface of the bat is unlikely to turn to face towards the same field when the contribution to the resultant bat-head speed is generated more by the translational component of the bathead speed than by the rotational component